Gender-Inclusive Ecological Transitions in Music Education : Repoliticising the Production of Public Spaces for Musical Heritage - Palanchoke, Pushpa; Treacy, Danielle; Westerlund, Heidi (Springer, 2026)
While sustainability is often framed as an environmental issue, and research on sustainability in music and music education largely focuses on preserving musical ecosystems, this chapter considers sustainability in terms of the social production of public musical spaces, particularly in relation to gender equality. More specifically, it promotes gender inclusive ecological transitions in the musical heritage contexts of contemporary Nepal, and thereby more systemic support towards sustainability in the whole of society. Through an interview case study with indigenous Newa women in the Kathmandu Valley, who continued to make music following their participation in an inclusionary activist intervention, we explore the complex gender politics of music making and the barriers the women face participating in traditionally male-dominated musical spaces. By reframing musical heritage as an evolving and contested political space, as illustrated through the Newa women’s narratives, the chapter calls for critical rethinking to move beyond monolithic traditions, arguing that women’s inclusion in public heritage practices can systematically contribute to sustainability.
Keywords: kestävä kehitys; musiikkikasvatus; sukupuoli; naisen asema; tasa-arvo; osallistuminen; koulutus; Nepal